Pengaruh Influencer Marketing terhadap Keputusan Pembelian (Survei pada Konsumen Ms Glow di Sumedang) - Yusanda, Eliana; Halim, Prihartono Aksan (Ekonomis: Journal of Economics and Business, 2024)
This research aims to find out how big the effect of influencer marketing is on purchasing decisions for MS Glow products in Sumedang. This research used a descriptive quantitative approach with a population of 1,458 people and a sample of 94 people using the Slovin formula. Data was collected using an online survey using a Likert scale. Data analysis uses simple regression. The research results show that there is a significant influence between the influencer marketing variable on the purchasing decision variable.